EL OJO DEL CÍCLOPE. Comentarios críticos a propósito del proceso de globalización - Massardo, Jaime (Ariadna Ediciones, 2008)
Essays on the world political situation in times of globalization and the challenges of the subalterns for their struggle against capitalism